2021
DOI: 10.18632/aging.202829
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin attenuates smoking-induced atherosclerosis by activating the Nrf2 pathway via NLRP3 inflammasomes in endothelial cells

Abstract: Substantial evidence suggests that the effects of smoking in atherosclerosis are associated with inflammation mediated by endothelial cells. However, the mechanisms and potential drug therapies for smoking-induced atherosclerosis remain to be clarified. Considering that melatonin exerts beneficial effects in cardiovascular diseases, we examined its effects on cigarette smoke-induced vascular injury. We found that cigarette smoke extract (CSE) treatment induced NLRP3-related pyroptosis in human aortic endotheli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 56 publications
2
30
0
Order By: Relevance
“…The etiology of atherosclerosis is more complex than previously thought, and its risk factors include hypertension, hyperlipidemia, heavy smoking, diabetes, and genetic predisposition ( Lien et al, 2020 ; Wang and Ge, 2021 ; Zhao et al, 2021 ). Generally, different factors interact and converge to affect the formation of foam cells and the maintenance of vascular inflammation, thereby promoting the occurrence of atherosclerosis ( Poznyak et al, 2020a ).…”
Section: Introductionmentioning
confidence: 99%
“…The etiology of atherosclerosis is more complex than previously thought, and its risk factors include hypertension, hyperlipidemia, heavy smoking, diabetes, and genetic predisposition ( Lien et al, 2020 ; Wang and Ge, 2021 ; Zhao et al, 2021 ). Generally, different factors interact and converge to affect the formation of foam cells and the maintenance of vascular inflammation, thereby promoting the occurrence of atherosclerosis ( Poznyak et al, 2020a ).…”
Section: Introductionmentioning
confidence: 99%
“…We and others previously found that by inhibiting NLRP3 signaling via Nrf2 signaling activation, endothelial cells were protected against stress from cigarette smoke extract ( Hu et al, 2018 ; Zhao Z. et al, 2021 ; Jin et al, 2021 ). A series of studies found that stressors, including smoking and high glucose, stimulated inflammation in vascular cells via Nrf2 downregulation ( Miao et al, 2013 ; Wang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 97%
“…The decreased AS plaque size and vulnerability were determined in atherosclerotic mouse model treated with melatonin. Reduced activation of NLRP3 inflammasome and maturation of IL-1 β were also found in atherosclerotic lesions ( Zhao Z. et al, 2021 ). Ma et al showed that melatonin partially prevented atherosclerotic progression through inducing mitophagy and attenuating Sirt3/FOXO3a/Parkin-mediated NLRP3 inflammasome activation ( Ma et al, 2018 ).…”
Section: Inhibition Of Nlrp3 Inflammasome Reduces Asmentioning
confidence: 99%